Role of Agricultural Sector and Quality of Its Production Factor in Indonesia: An Application of Input-Output Analysis and Panel Model - Pramana, Anugerah Surya; Wicaksono, Ditto Satrio; Fajar, Huda M. (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Indonesia has been known as the largest agricultural country in Southeast Asia. However, the sector contribution to national output has declined. This indicates a low interconnection between agriculture and the other sectors despite the sector’s significant potential to stimulate other industries’ output through strong backward and forward linkages. This condition is caused by the role of production factors that determine agricultural output. Therefore, the research aims to analyse agriculture’s linkages with other sectors and to assess the effects its production factor on agricultural output. Using Input–Output multiplier analysis, it is found the agriculture, forestry, and fisheries sector is the largest absorber of labour in Indonesia. This sector is predominantly consumed directly by households. Meanwhile, panel model results for 2010–2024 show that increases in labour without accompanying improvements in quality have a negative effect, whereas investment and credit, as manifestations of capital, have positive effects on agricultural gross value added. Policy implications include prioritizing skills development and improving access to credit and investment to foster adoption of productivity-enhancing technologies, thereby enabling the agricultural sector to grow and exert greater influence on other sectors and on the national economy.